Pengaruh Current Ratio, Inventory Turnover dan Debt to Equity terhadap Return on Asset - Sindik Widati; Tania Dwi Hartini (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2021)
This study aims to determine the effect of Current Ratio, Inventory Turnover and Debt to Equity on Return on Asset Practice in Property and Real Estate companies listed on the Indonesia Stock Exchange period 2017-2019. The research method used in this study is a quantitative method. The data used are secondary data in the form of financial statements and annual reports. The sampling technique in this study was purposive sampling method in which sample selection was based on certain criteria. The study population used was 64, the research sample of 24 companies. The analysis technique in this study uses multiple linear regression analysis. The analysis shows that Current Ratio do not affect the Return on Asset, Inventory Turnover do not affect the Return on Asset and Debt to Equity do not affect the Return on Asset.